Anthropometric standards for Australian primary school children: Towards a system for monitoring and supporting children's development. Issue 3 (March 2017) - Cochrane, Thomas; Davey, Rachel C.; de Castella, F. Robert
Abstract: Objectives: To provide two foundation elements of a proposed new system to support children's physical and body status development throughout primary school: (a) age and gender appropriate achievement (anthropometric) standards and (b) a system of monitoring, feedback and support. Design: Repeated cross-sectional sampling involving 91 schools across 5 Australian States and Territories between 2000 and 2011. Methods: Anthropometric data from 29, 928 (14, 643 girls, 15, 285 boys) Australian children aged between 5 and 12.5 years were used to develop progression standards (norm centiles) covering the primary school years. Measures used were: height, weight, body mass index, per cent body fat, grip strength, standing long jump, cardiorespiratory fitness, sit-ups and sit-and-reach. These norms were then used to develop a Physical Activity and Lifestyle Management (PALM) system that could form the basis for progression, monitoring and reporting of anthropometric achievement standards for children. Results: Tables and representative centile curves (3rd, 15th, 50th, 85th and 97th) for each gender and half-year age group were produced. An illustrative example of the PALM system in operation was also provided. Conclusions: Our research provides gender and half-year age specific anthropometric standards for Australian primary school children. Furthermore, we have developed a monitoring and progression system that could be embedded in school communities to help address the prevalence of underweight, overweight and obesity and decline in physical fitness standards. The proposed system is designed on behalf of children and families and would be administered through school settings. Change, where needed, would be delivered by the supporting school community.